USING GOOGLE DOCS FOR COLLABORATIVE WRITING IN TEACHING WRITING DESCRIPTIVE TEXT TO ENGLISH DEPARTMENT STUDENTS - Tenty Metilia; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
AbstractThis paper discusses how to apply Google Docs for collaborative writing in teaching writing to English Department students. Google docs as a feature Google served for all its users can be used collaborative writing in which all students in one class can contribute to make a good writing. Collaborative writing means that students write a text and sharing ideas with others students and it will be corrected and supported by others students By using Google Docs for collaborative writing, students can interact and write together with other students in developing their writing. They can give comments to other students and edit other students’ drafts at the same time. It will help them to get more ideas in writing as they combine their ideas with others ideas. Keywords: Writing, Collaborative Writing, Descriptive Text, Google Docs